2015
DOI: 10.1017/s1466252315000055
|View full text |Cite
|
Sign up to set email alerts
|

The two sides of border disease in Pyrenean chamois (Rupicapra pyrenaica): silent persistence and population collapse

Abstract: In 2001, border disease virus (BDV) was identified as the cause of a previously unreported disease in Pyrenean chamois (Rupicapra pyrenaica) in Spain. Since then, the disease has caused a dramatic decrease, and in some cases collapse, of chamois populations and has expanded to nearly the entire distribution area in the Pyrenees. Chamois BDV was characterized as BDV-4 genotype and experimental studies confirmed that it was the primary agent of the disease. The infection has become endemic in the Central and Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…These outbreaks have decimated several Pyrenean chamois populations, with mortalities ranging from 40% to 85% [16]. After the severe BDV-4 outbreaks, different epidemiological scenarios have appeared in the Pyrenees, having a prolonged negative impact on host population dynamics in some areas [17].…”
Section: Introductionmentioning
confidence: 99%
“…These outbreaks have decimated several Pyrenean chamois populations, with mortalities ranging from 40% to 85% [16]. After the severe BDV-4 outbreaks, different epidemiological scenarios have appeared in the Pyrenees, having a prolonged negative impact on host population dynamics in some areas [17].…”
Section: Introductionmentioning
confidence: 99%
“…The etiological agent of these infections was classified into the BDV4 genogroup (Arnal et al, 2004). Fifteen years after the first outbreak, pestivirus are still circulating among Pyrenean chamois and this situation suggests an endemic and asymptomatic virus circulation in some areas (Marco et al, 2015). Although Pyrenean chamois' sympatric ruminant species have been suspected to be involved in the maintenance of the virus in the Pyrenees, low antibody seroprevalences, absence of PI individuals and no clinical infections have been reported (Fernández-Sirera et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…After 17 years since the first outbreak of border disease (BD) in Pyrenean chamois and at least since 28 years of pestivirus presence in Pyrenean chamois populations, several studies have investigated the factors that rule the diversity of the epidemiological scenarios (Fernández‐Sirera et al, ; Marco et al, ; Martin et al, ; Pioz et al, ). This study unravel that pathogen virulence is most probably the main factor driving disease presentation and impact on chamois populations.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies carried out in France, Andorra, and Spain have shown different epidemiological scenarios in chamois populations (Pioz et al, ; Marco et al, ; Martin et al, ). Pestivirus infections in chamois populations from the Pyrenees mainly cause mortality outbreaks with different impacts at the population level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation